Peningkatan Keterampilan Menulis Artikel Populer pada Mahasiswa Melalui Program Satu Mahasiswa Satu Karya (SAMA SAYA) - Hamidulloh Ibda (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Writing popular articles in the mass media is admittedly very difficult for students. In addition to adjusting the latest issues, popular articles in the mass media must also be adjusted to diction, spelling, mass media characters, and free of plagiarism. The purpose of this study was to improve the skills of writing popular articles on students through the One Student One Creation program (SAMA SAYA). The sample in this study were 42 second semester students of the Islamic Education program at STAINU Temanggung academic year 2018-2019. This action research was designed with the Kemmis and Mc Taggart models, namely planning, action, observation, and reflection. The results of the study indicate that the SAMA SAYA program can improve popular article writing skills. Starting the aspect of determining the current problem / issue, from 14 students (33.3 percent) to become 40 students (95.2 percent), determining interesting titles from 18 students completed (42.8 percent) increased 39 students completed (92.8 percent), the selection of correct diction, from 12 students completed (28.5 percent) to 38 students completed (90.4 percent). In the aspect of using PEUBI rules which initially 14 students completed (33.3 percent) to 30 students completed (71.4 percent), understanding the character of mass media initially 5 students completed (11.9 percent) to 40 students completed (95.2 percent ), not plagiarism under 25 percent as many as 12 students completed (28.5 percent) increased to 37 students (88.0 percent).